A comment on a fine-grained description of evaporating black holes with baby universes - Norihiro Iizuka; Akihiro Miyata; Tomonori Ugajin (Journal of High Energy Physics, 2022)
Abstract We study a partially fine-grained description of an evaporating black hole by introducing an open baby universe with a boundary. Since the Page’s calculation of the entropy of Hawking radiation involves an ensemble average over a class of states, one can formally obtain a fine-grained state by purifying this setup. For AdS black holes with a holographic dual, this purification amounts to introducing an additional boundary (i.e., baby universe) and then connecting it to the original black hole through an Einstein-Rosen bridge. We uncover several details of this setup. As applications, we briefly discuss how this baby universe modifies the semi-classical gravitational Gauss law as well as the gravitational dressing of operators behind the horizon.